MUSABAQAH TILAWAH AL-QUR’AN DI INDONESIA (FESTIVALISASI AL-QUR’AN SEBAGAI BENTUK RESEPSI ESTETIS) - Jannah, Miftahul (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2016)
One of the regular agenda which is held in Indonesia is Musabaqah Tilawah al-Qur?an (MTQ). This agenda carried out at regional, national, even internasional level. MTQ can be said as the biggest religious event or festival which celebrated by Moslems in Indonesia. The present of this Qur?anic competition is very interesting because it is one of the esthetic reception from society and was declared by the government as a regular agenda. All walks of life be able to join and participate at it for cheering up this biennial activity. This article discusses about MTQ as Indonesian reception of the Qur?an in esthetic aspect. The conclusion says that MTQ is not only as medium to stimulate Indonesian people for reciting Qur?an beautifully but also as spirit to understand the meaning of Qur?anic verses itself hopefully.